2001
DOI: 10.1287/ijoc.13.2.157.10520
|View full text |Cite
|
Sign up to set email alerts
|

Non-Approximability Results for Scheduling Problems with Minsum Criteria

Abstract: We provide several non-approximability results for deterministic scheduling problems whose objective is to minimize the total job completion time. Unless P = N P, none of the problems under consideration can be approximated in polynomial time within arbitrarily good precision. Most of our results are derived by APX-hardness proofs. We show that, whereas scheduling on unrelated machines with unit weights is polynomially solvable, the problem becomes APX-hard if release dates or weights are added. We further sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2002
2002
2009
2009

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(31 citation statements)
references
References 20 publications
0
31
0
Order By: Relevance
“…They show that for any of these problems with integer processing times, there is a polynomialtime algorithm that determines whether a schedule S with C max (S) = 3 exists; by contrast, unless P = N P, it is impossible to verify in polynomial time whether there exists a schedule S with C max (S) = 4. Thus, the existence of a polynomial-time approximation algorithm with a worst-case ratio strictly less than 5/4 would imply that P = N P. Hoogeveen et al (2001) demonstrate that many scheduling problems with a variable number of machines to minimize the sum of the completion times (including the flow shop and the open shop) are Max SNP-hard, and this implies that for any of these problems the existence of a PTAS would imply that P = N P.…”
Section: Shop Schedulingmentioning
confidence: 94%
“…They show that for any of these problems with integer processing times, there is a polynomialtime algorithm that determines whether a schedule S with C max (S) = 3 exists; by contrast, unless P = N P, it is impossible to verify in polynomial time whether there exists a schedule S with C max (S) = 4. Thus, the existence of a polynomial-time approximation algorithm with a worst-case ratio strictly less than 5/4 would imply that P = N P. Hoogeveen et al (2001) demonstrate that many scheduling problems with a variable number of machines to minimize the sum of the completion times (including the flow shop and the open shop) are Max SNP-hard, and this implies that for any of these problems the existence of a PTAS would imply that P = N P.…”
Section: Shop Schedulingmentioning
confidence: 94%
“…This problem is a special case of the data migration problem [7]. Open shop scheduling problem has been studied in [3,12,20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Queyranne & Sviridenko [15] showed that an approximation algorithm for the above mentioned problems that produces a schedule with makespan a factor O(ρ) away from the lower bound lb can be used to obtain a O(ρ)-approximation algorithms for other objectives, including the sum of weighted completion times. The only known inapproximability result is by Hoogeveen, Schuurman & Woeginger [7], who showed that F || C j is NP-hard to approximate within a ratio better than 1 + for some small > 0.…”
Section: Literature Reviewmentioning
confidence: 99%